In vaccinated individuals serum bactericidal activity against B meningococci is abrogated by C5 inhibition but not by inhibition of the alternative complement pathway - Ispasanie, Emma; Muri, Lukas; Schmid, Marc; Schubart, Anna; Thorburn, Christine; Zamurovic, Natasa; Holbro, Thomas; Kammüller, Michael; Pluschke, Gerd (Frontiers in Immunology, 2023)
Introduction Several diseases caused by the dysregulation of complement activation can be treated with inhibitors of the complement components C5 and/or C3. However, complement is required for serum bactericidal activity (SBA) against encapsulated Gram-negative bacteria. Therefore, C3 and C5 inhibition increases the risk of invasive disease, in particular by Neisseria meningitidis. As inhibitors against complement components other than C3 and C5 may carry a reduced risk of infection, we compared the effect of inhibitors targeting the terminal pathway (C5), the central complement component C3, the alternative pathway (FB and FD), and the lectin pathway (MASP-2) on SBA against serogroup B meningococci. Methods Serum from adults was collected before and after vaccination with the meningococcal serogroup B vaccine 4CMenB and tested for meningococcal killing. Since the B capsular polysaccharide is structurally similar to certain human polysaccharides, 4CMenB was designed to elicit antibodies against meningococcal outer membrane proteins. Results While only a few pre-vaccination sera showed SBA against the tested B meningococcal isolates, 4CMenB vaccination induced potent complement-activating IgG titers against isolates expressing a matching allele of the bacterial cell surface-exposed factor H-binding protein (fHbp). SBA triggered by these cell surface protein-specific antibodies was blocked by C5 and reduced by C3 inhibition, whereas alternative (factor B and D) and lectin (MASP-2) pathway inhibitors had no effect on the SBA of post-4CMenB vaccination sera. Discussion Compared to the SBA triggered by A,C,W,Y capsule polysaccharide conjugate vaccination, SBA against B meningococci expressing a matching fHbp allele was remarkably resilient against the alternative pathway inhibition.